Multi-purpose forages potential to enhancing mixed smallholder farming productivity and food security in Malawi - Bekele, Regassa; Hami, Joseph; Homann-kee Tui, Sabine; Mwendia, Solomon; Notenbaert, An (2025)
The livestock sector is integral to Malawi’s mixed farming systems, contributing 22–30% of GDP and employing over 80% of the labor force. However, a lack of scientific information on integrating mixed farming systems, coupled with inadequate stakeholder coordination, has hindered its potential to enhance farm productivity. This challenge is exacerbated by population growth, which has led to land fragmentation among smallholder farmers. Farmers and extension workers often fear that cultivating forages will reduce land available for food crops, prioritizing crop production at the expense of livestock feed. Consequently, smallholder farmers face low livestock productivity due to insufficient quality feed, while continuous plowing has resulted in soil erosion, fertility loss, and declining crop yields—ultimately reducing overall farm productivity and perpetuating household food insecurity. To address these challenges, a reconnaissance survey was conducted in December 2024 to identify opportunities for integrating multipurpose forages into Malawi’s mixed farming systems. The study team assessed predominant farming systems, identified challenges, and gathered stakeholder perspectives on cultivated and native forages. Field observations and discussions with farmers, researchers, government officials, development agencies, and private sectors across Malawi’s northern, central, and southern regions revealed opportunities for forage integration. Forage production strategies such as backyard planting, intercropping, alley cropping, crop rotation, agroforestry, and Push-Pull systems are recommended as entry points for improving livestock feed availability while simultaneously enhancing soil fertility, reducing erosion, and controlling pests. Prioritizing the development of improved forage varieties and robust seed supply systems are also recommended to support these strategies. The findings provide valuable insights for policymakers, researchers, farmers, private sector actors, and international donors, offering actionable pathways to unlock the potential of mixed farming systems in Malawi.